Peningkatan Kualitas Lingkungan Fisik Alun-Alun Kota Yogyakarta Sebagai Ruang Publik Kota - Sigit Dwiananto A (The Institute for Research and Community Services, Institut Teknologi Bandung, 2003)
As parts of Kraton, the Squares of Yogyakarta have been through many changes. They are no longer considered as a transition between sacred space (Kraton) and profane space (the settlement outside the beteng), but as a public space to be utilized by everyone. This can be seen with the growing functional activities that replace cultural ones. This result is inevitable deterioration of the physical quality of the squares. This paper explores the ideas of upgrading the physical quality of the squares using design criteria and components that have been commonly acknowledged in designing public space. Findings show that the deviation of uses, the declined condition of design components, conflicts within activities, and the lack of maintenance, have caused the deteriorating quality of spaces. Thus, the design of the squares should emphasize on spatial arrangement of supporting activities and the reinterpretation of the image and identity of the squares as an integral part of Kraton.Keywords: public space, physical environment, design criteria and design components, supporting activities, image and identity